Decentralizing education resources: School grants in Senegal - Pedro Carneiro; Oswald Koussihouede; Nathalie Lahire; Costas Meghir; Corina Mommaerts (Yale University, Economic Growth Center, 2015)
The impact of school resources on the quality of education in developing countries may depend crucially on whether resources are targeted efficiently. In this paper we use a randomized experiment to analyze the impact of a school grants program in Senegal, which decentralized a portion of the country's education budget. We find large positive effects on test scores at younger grades that persist at least two years. We show that these effects are concentrated among schools that focused funds on human resources improvements rather than school materials, suggesting that teachers and principals may be a central determinant of school quality.
Keywords: H52; I22; I25; O15; 330; Quality of Education; Decentralization; School Resources; Child Development; Clustered Randomized Control Trials